Riparian zones (PPAs) in the landscape of the sub-basins of the Corumbataí and Piracicaba rivers in front of the New Forest Code (NVPL) of 2012 - Casarin, Laura Piacentini (2023)
In the State of São Paulo, the scarcity of water resources has become a constant agenda in water security discussions. Within this context, the protection and recovery of forest cover play a key role in increasing the resilience of water supply systems. In order to contribute to the development of specific protection and restoration policies for the dynamics of regional deforestation, the objective was to evaluate the suppression of riparian forest in Permanent Preservation Areas (PPAs) and its relationship with the types of land use and land cover, as well as the impact of the Native Vegetation Protection Law (NVPL) on these standards. For this, we analyzed the spatial and temporal evolution of the coverage of riparian PPAs in the municipalities of Corumbataí, Rio Claro, and Piracicaba, inserted in the sub-basins of the Corumbataí River and Piracicaba River, through the object-oriented classification of RapidEye high spatial resolution satellite imagery for the years 2009, 2014 and 2019, and geoprocessing techniques. The analysis involved aspects related to land use and land cover, the landscape structure, and the conditions and configuration of the PPAs. It was found that a process of fragmentation is taking place within these areas of permanent preservation. The agropastoral system is the factor with the greatest influence on impacts on the PPAs, in addition to the predominance of pasture and sugarcane in about 50% and 30%, respectively, of the evaluated areas. However, the impacts arising from the implementation of the NVPL were not homogeneous among the classes of anthropic use, bringing different dynamics of recovery of riparian forest and the emergence of new deforestation in all classes of rural properties assessed. Irregular situations in relation to legislation and environmental preservation were detected, mainly in the class of small rural properties (up to 4 Fiscal Modules) which concentrate the largest amount of water bodies, between 30% and 50% of PPAs, in both sub-basins. In addition to pastures, the type of land use that requires greater attention due to expansion trends in PPAs was forestry in the three municipalities, an indication of economic influence in the region. The results help to understand the first impacts of the NVPL on the patterns of land use and cover of the PPAs, revealing the existence of distinct dynamics within the same type of land use and classes of rural properties, as well as the influence of the history of colonization and land occupation in the region. Understanding the regional dynamics of the use and occupation of PPAs, the characteristics of their governance policies, and agricultural production in the area is essential to direct conservation efforts and maximize their efficiency.